Analisis Produksi dan Pendapatan Petani Usahatani Padi yang Menggunakan Metode Salibu dan Konvensional di Kecamatan Pariangan Kabupaten Tanah Datar Provinsi Sumatera Barat - Fadhilah, Miftahul; Rochdiani, Dini; Trimo, Lucyana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Rice is one of the main commodities in Indonesian society. To increase production and income, various methods and technologies can be used. One method that can be applied is the rice salibu method. This research aims to: Identify factors that influence farmers in implementing salibu method in Pariangan District. This research uses logistic regression analysis techniques. The results of the research show that the factors that influence farmers in implementing salibu method are frequency of presence of farmers in farmer group activities and farmer income.